Oral selinexor-dexamethasone for triple-class refractory multiple myeloma - Chari, Ajai; Raab, Marc-Steffen (The New England journal of medicine, 2019)
BACKGROUND Selinexor, a selective inhibitor of nuclear export compound that blocks exportin 1 (XPO1) and forces nuclear accumulation and activation of tumor suppressor proteins, inhibits nuclear factor κB, and reduces oncoprotein messenger RNA translation, is a potential novel treatment for myeloma that is refractory to current therapeutic options. - METHODS We administered oral selinexor (80 mg) plus dexamethasone (20 mg) twice weekly to patients with myeloma who had previous exposure to bortezomib, carfilzomib, lena lidomide, pomalidomide, daratumumab, and an alkylating agent and had disease refractory to at least one proteasome inhibitor, one immunomodulatory agent, and daratumumab (triple-class refractory). The primary end point was overall response, defined as a partial response or better, with response assessed by an independent review committee. Clinical benefit, defined as a minimal response or better, was a secondary end point. The authors’ full names, academic degrees, and affiliations are listed in the Appendix. Address reprint requests to Dr. Jagannath at the Tisch Cancer Institute, Icahn School of Medicine at Mount Sinai, 1470 Madison Ave., 3rd Fl., New York, NY 10029, or at s undar.jagannath mountsinai. org. Drs. Richardson and Jagannath contributed equally to this article. N Engl J Med 2019;381:727-38. DOI: 10.1056/NEJMoa1903455 Copyright © 2019 Massachusetts Medical Society. - RESULTS A total of 122 patients in the United States and Europe were included in the modified intention-to-treat population (primary analysis), and 123 were included in the safety population. The median age was 65 years, and the median number of previous regi mens was 7; a total of 53% of the patients had high-risk cytogenetic abnormalities. A partial response or better was observed in 26% of patients (95% confidence interval, 19 to 35), including two stringent complete responses; 39% of patients had a minimal response or better. The median duration of response was 4.4 months, median progres sion-free survival was 3.7 months, and median overall survival was 8.6 months. Fa tigue, nausea, and decreased appetite were common and were typically grade 1 or 2 (grade 3 events were noted in up to 25% of patients, and no grade 4 events were re ported). Thrombocytopenia occurred in 73% of the patients (grade 3 in 25% and grade 4 in 33%). Thrombocytopenia led to bleeding events of grade 3 or higher in 6 patients. - CONCLUSIONS Selinexor-dexamethasone resulted in objective treatment responses in patients with myeloma refractory to currently available therapies. (Funded by Karyopharm Thera peutics; STORM ClinicalTrials.gov number, NCT02336815.)
Gesehen am 09.12.2019